Pilot longitudinal mosquito surveillance study in the Danube Delta Biosphere Reserve and the first reports of Anopheles algeriensis Theobald, 1903 and Aedes hungaricus Mihályi, 1955 for Romania. Issue 1 (December 2016) - Török, Edina; Tomazatos, Alexandru; Cadar, Daniel; Horváth, Cintia; Keresztes, Lujza; Jansen, Stephanie; Becker, Norbert; Kaiser, Achim; Popescu, Octavian; Schmidt-Chanasit, Jonas; Jöst, Hanna; Lühken, Renke
Abstract Background Mosquito-borne viruses (moboviruses) are of growing importance in many countries of Europe. In Romania and especially in the Danube Delta Biosphere Reserve (DDBR), mosquito and mobovirus surveillance are not performed on a regular basis. However, this type of study is crucially needed to evaluate the risk of pathogen transmission, to understand the ecology of emerging moboviruses, or to plan vector control programmes. Methods We initiated a longitudinal mosquito surveillance study with carbon dioxide-baited Heavy Duty Encephalitis Vector Survey traps at four sampling sites to analyse the spatio-temporal pattern of the (i) mosquito species composition and diversity, (ii) functional groups of mosquitoes (oviposition sites, overwintering stage, and number of generations), and (iii) the occurrence of potential West Nile virus (WNV) vectors. Results During 2014, a total of 240, 546 female mosquitoes were collected. All species were identified using morphological characteristics and further confirmed by mitochondrial cytochromec oxidase subunit I (COI) gene analysis of selected specimens. The two most common taxa wereCoquilettidia richiardii (40.9 %) andAnopheles hyrcanus (34.1 %), followed byCulex pipiens (sensu lato ) (s.l .)/Cx. torrentium (7.7 %), Aedes caspius (5.7 %), Cx. modestus (4.0 %), An. maculipennis (s.l .) (3.9 %), andAe. vexans (3.0 %). A further seven species were less common in the area studied, including two new records for Romania:An. algeriensis andAe. hungaricus . Phylogenetic analysis of COI gene demonstrated the evolutionary relatedness of most species with specimens of the same species collected in other European regions, exceptAe. detritus andAn. algeriensis, which exhibited high genetic diversity. Due to the dominance ofCq. richiardii andAn. hyrcanus (75 % of all collected specimens), the overall phenology and temporal pattern of functional groups basically followed the phenology of both species. A huge proportion of the mosquito population in the course of the entire sampling period can be classified as potential WNV vectors. With 40 % of all collected specimens, the most frequent speciesCq. richiardii is probably the most important vector of WNV in the DDBR. Conclusion This is the first DNA-barcoding supported analysis of the mosquito fauna in the DDBR. The detection of two new species highlights the lack of knowledge about the mosquito fauna in Romania and in the DDBR in particular. The results provide detailed insights into the spatial-temporal mosquito species composition, which might lead to a better understanding of mobovirus activity in Romania and thus, can be used for the development of vector control programs.